SEJARAH PERKEMBANGAN SENI PERTUNJUKAN SILATOTAR-OTAR DI KABUPATEN SAMBAS KALIMANTAN BARAT - Wardani, Yessica Sisilya; Istiandini, Winda; Fretisari, Imma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis willingness to research to dig back Arts Otar-Otar, and to explore the process of historical development of the Otar-Otar became performance art, due to lack of documentation against Otar-Otar. The purpose of this research is to 1. Describe the history of performance art silat Otar-Otar 1992-2015 in Sambas Regency, West Kalimantan. 2. Describe the development of a form of martial arts performing arts specialties Otar-Otar in Sambas Regency, West Kalimantan. 3. Describe the draft implementation from performing arts Otar-Otar of Sambas Regency, West Kalimantan. The theory used in this research analysis is a theory about the dance, dance history, cultural anthropology, traditional dance, pencak silat, performing arts. This research using the method of analysis of history. This form of research is qualitative. The research approach using the approach of etnokoreologi. The data source in this research in the form of the results of the interview against the speaker related to and find out about the development historical of the performing arts Otar-Otar In Sambas Regency, West Kalimantan. Data collection techniques in the form of observation, interview and documentation. The technique of testing the validity of the data used is an extension of the observation, triangulation data.  Keywords: History, Performing Arts, Otar-Otar